SANKSI KERJA SOSIAL, SEBUAH ALTERNATIF PENALISASI TERHADAP PELANGGARAN LALU LINTAS DI KOTA PAREPARE - Firmansyah (Madani Legal Review, 2019)
Social work sanctions is an alternative in handling traffic violations without going through a litigation process, this research aims; First, to find out the right strategies related to social work sanctions. Second, to find out the factors that influence the implementation of social work sanctions and finally to find out the impact of the application of social work sanctions. The research method used is a socio-normative research method. Data collection techniques for library research and interviews. The results of this study indicate that the strategies is used in implementing social work sanctions are; Field survey, socialization Collaborate with the police to conduct sweeping on the object of research, carry out social / social work sanctions and install stickers to control and there needs to be a conscious area or traffic order. namely the existence of the concept of ultimum Remedium. It’s mean that criminal is the last step and the Discretion is a power or authority that is carried out based on the law for consideration and belief and emphasizes moral considerations rather than legal considerations. The inhibiting factors are; Written rules or regulations / substances that do not yet exist, lack of socialization and legal culture or attitudes of both the community and the police are still low regarding legal issues. Finally, the impact of the implementation is the creation of rules or laws that specifically regulate the issue of social work sanctions. The next thing is the creation of the Community Police Concept